2009
DOI: 10.1038/clpt.2009.216
|View full text |Cite
|
Sign up to set email alerts
|

High Frequency of Occurrence of CYP2D6 Gene Duplication/Multiduplication Indicating Ultrarapid Metabolism Among Suicide Cases

Abstract: In Sweden, about 550 individuals die every year of drug intoxication. Many of these drugs are metabolized by CYP enzymes such as CYP2D6 and CYP2C19. A lack of these enzymes, resulting in poor metabolism, can lead to adverse reactions and even to fatality. On the other hand, an ultrarapid metabolism can lead to insufficient drug plasma concentration, resulting in failure of treatment, or it can lead to high concentrations of active/toxic metabolites. The aim of this project was to study the genetic profile of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
57
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(64 citation statements)
references
References 34 publications
4
57
1
Order By: Relevance
“…However, further research is needed to overcome the limitations inherent in the present design, including the control for potential biases derived from recruiting individuals who volunteer for this type of study. 12 Present findings seem to be in agreement with previous results showing that UMs are more frequent among suicide cases, 13 persistent mood-disordered patients 14 and among women with symptoms of depression, 15 which usually overlap with ED. [16][17][18] In addition, we have previously reported that PMs are less frequent among schizophrenic patients than among healthy subjects (2.3 vs 8.5%, respectively), 19 which would be in accordance with lower scores on a measure of risk to psychopathology or general distress also found among PM healthy volunteers.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, further research is needed to overcome the limitations inherent in the present design, including the control for potential biases derived from recruiting individuals who volunteer for this type of study. 12 Present findings seem to be in agreement with previous results showing that UMs are more frequent among suicide cases, 13 persistent mood-disordered patients 14 and among women with symptoms of depression, 15 which usually overlap with ED. [16][17][18] In addition, we have previously reported that PMs are less frequent among schizophrenic patients than among healthy subjects (2.3 vs 8.5%, respectively), 19 which would be in accordance with lower scores on a measure of risk to psychopathology or general distress also found among PM healthy volunteers.…”
Section: Discussionsupporting
confidence: 93%
“…11 Moreover, we have shown that PMs appear to present lower psychopathology compared with EMs. [11][12] Consistently, UMs appear more frequent among individuals who commit suicide, 13 or who present persistent mood disorder, 14 as well as among women with postpartum depression. 15 In addition, altered serotonin neurotransmission and associated comorbid affective disorders are frequently described in ED.…”
Section: Introductionmentioning
confidence: 85%
“…In another Finnish study, 33 cases positive for tramadol were genotyped and 12% PMs and 12% UMs were found [58]. Zackrisson et al [38] have in an earlier Swedish study genotyped 239 intoxication suicide cases, 254 violent suicide cases and 205 natural death cases. The mean number of PMs found in these three materials was 6.8% and the corresponding figure for UMs was 2.6% [38].…”
Section: Discussionmentioning
confidence: 97%
“…Three single nucleotide polymorphisms (SNPs), *3, *4 and *6, were included in the genotyping of CYP2D6 (Table 1). These alleles were identified by PCR and pyrosequencing as earlier described [37] with some minor modifications [38].…”
Section: Genotyping For Cyp2d6mentioning
confidence: 99%
See 1 more Smart Citation